Hypoxia: Adaptation Mechanisms and Their Impact on Organs - Rifda El Mahroos; Shellya Puti Sudesty; Rifka Wangiana Yulia Putri (Journal of Diverse Medical Research : Medicosphere, 2026)
Background: Hypoxia is a decrease in tissue oxygen that induces the activation of hypoxia-inducible factor (HIF) and cellular responses such as metabolic changes, angiogenesis, and inflammatory modulation. This initial adaptive response can become maladaptive with prolonged or repeated exposure. Methods: This article is a narrative review that examines literature from 2015–2025 from PubMed, ScienceDirect, and Google Scholar. Searches were conducted using keywords related to "hypoxia," "hypoxia-inducible factor (HIF)," "cellular adaptation," and "organ impacts," with selection based on relevance and scientific quality. Discussion: Hypoxia has various exposure patterns (acute, chronic, and intermittent) that trigger a body response through the activation of oxygen sensors and gene regulation by HIF. In the initial stages, the body attempts to maintain stable cell function. However, prolonged or repeated exposure renders this adaptive response ineffective and leads to tissue disruption. These impacts are seen in various organs, such as changes in heart structure, pulmonary vascular alterations, an increased tendency for fibrosis in the liver and kidneys, and a decreased integrity of the gastrointestinal epithelial barrier, all of which can contribute to disease. Conclusion: Hypoxia is a complex biological stimulus with dualistic effects that depend on the duration and intensity of exposure. This understanding is crucial for improving diagnostic and therapeutic strategies related to hypoxia. Keywords: hypoxia, HIF pathway, oxidative stress, organ dysfunction, inflammation